MOTIVATION MECHANISM OF WORK BEHAVIOUR ENHANCEMENT OF HOSPITALITY INDUSTRY EMPLOYEES - MAKRINOVA, Elena I.; GRIGORIEVA, Viktoriya V. (Journal of Environmental Management and Tourism, 2016)
The article substantiates the timeliness, significance and necessity of the development of the motivation mechanism of work behaviour enhancement of the hospitality industry employees. On the basis of the author’s classification of labour behaviour motivators, the motivation mechanism model of its enhancement as an open system has been developed and its formation stages and targets under the scenarios approach have been defined. Six groups of motivators of labour activity of hospitality industry employees are reasonable to monitor: material motivation (incentives), wide social motivation, participation, motivation of affiliation, procedural motivation, motivation to self-actualization. The factors discouraging labour behaviour of hospitality industry employees have been systematized and the mitigating measures have been identified. The article proved that the path to effective management of work behaviour lies through understanding each employee’s incentives, their personal work motivation, which is a set of external and internal forces (incentives) encouraging the implementation of certain work efforts. The authors present an argument in favour of the complex use of various forms of incentives (material and non-material) which can be applied to the hospitality industry employees.
Keywords: hospitality industry; motivation mechanism; motivation; labor; labor behavior